2021
DOI: 10.1111/jfpp.15393
|View full text |Cite
|
Sign up to set email alerts
|

Physicochemical, technological, and sensory characteristics of fresh multigrain pasta: A multicomponent mixture experiments approach

Abstract: Pasta is a popular food throughout the world and its quality can be measured mainly by its appearance, taste, and texture. The aim of this work was first to produce fresh multigrain pasta with a maximization of the sensorial properties and then evaluate the effects of the unconventional flours (rice, oat, and soy) on the physicochemical properties and sensory profile. Soy flour alone contributed to most modifications, such as an increase in yellow color (8.9-13.5, b* parameter), a decrease in the homogeneous a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 40 publications
(63 reference statements)
0
1
1
1
Order By: Relevance
“…The cooking time of fresh pasta showed no significant difference between the formulations studied, meaning BF did not interfere with the cooking time of the pasta. In the present study, the cooking time was shorter than cooking times previously observed for pasta with pigeon pea flour (Casagrandi et al, 1999), S. platensis (Lemes et al, 2012), and fresh multigrain pasta (rice, oat, and soy) (Oliveira Filho et al, 2021).…”
Section: Technological Characterizationcontrasting
confidence: 68%
See 1 more Smart Citation
“…The cooking time of fresh pasta showed no significant difference between the formulations studied, meaning BF did not interfere with the cooking time of the pasta. In the present study, the cooking time was shorter than cooking times previously observed for pasta with pigeon pea flour (Casagrandi et al, 1999), S. platensis (Lemes et al, 2012), and fresh multigrain pasta (rice, oat, and soy) (Oliveira Filho et al, 2021).…”
Section: Technological Characterizationcontrasting
confidence: 68%
“…There was lower water loss in fresh pasta with BF when compared to fresh pasta with S. platensis (Lemes et al, 2012). Except for the 15BF formulation, the volume displacement was lower than presented by Lemes et al (2012) for fresh pasta with S. platensis and higher than those reported by Oliveira Filho et al (2021) due to the presence of a matrix composed of rice, oat, and soy that participate more efficiently in the structuring of the fresh pasta.…”
Section: Technological Characterizationmentioning
confidence: 64%
“…Bu doğrultuda de Oliveira Filho vd. [120] yaptıkları çalışmada, yulaf ile zenginleştirilmiş makarna üreterek, ürünün fizikokimyasal ve duyusal profilini incelemeyi amaçlamışlardır. Yulaf un haline getirilerek makarnaya ikame edilmiştir.…”
Section: B Tahillar İle Yapilan çAlişmalarunclassified